Financial feasibility studies of eVTOL aircraft production project of PT XYZ - Senggoro A, Haryo; Oktofa S, Yudha (Enrichment : Journal of Management, 2024)
The growth of Transportation in Indonesia especially in cities led to increased destination time and traffic jams. As one of the solutions air taxis using electric Vertical Take-Off Landing (eVTOL) is advised. As a country capable of producing aircraft, PT XYZ seizes the chance to invest in the production of eVTOL in Indonesia. PT XYZ planned this project from 2024 to 2035 with an initial investment of $327,292,103.88 (USD). From 2024 to 2028 planned to expand its capital and from 2029 to 2035 PT XYZ planned to sell eVTOL aircraft in the domestic markets and international markets. Based on the financial projection of PT XYZ plan, this project is financially feasible because of a positive Net Present Value (NPV) of $209,542,512.94 and an Internal Rate of Return of 26.98%. This project has a payback period of 8 years and a profitability index of 1.49. Using the sensitivity analysis and Monte Carlo Simulation, the costs of goods sold and aircraft prices of this project affect the project’s NPV with an 80% chance of positive NPV